Estudo da cristalização de lactose em diferentes solventes - Brito, Ana Beatriz Neves (2007)
In the study of the lactose crystallization process, the nucleation phenomena and crystalline growth have been evaluated, when the systems were submitted to different solvent and operational conditions. The solubility s curves, for each of the solvents, were obtained experimentally and compared with theoretical data, serving as a basis for the crystallization processes. The main objective of the present work is to study the lactose crystallization process in solution through the partial change of the solvent. This change occurs through the addition of a second solvent, a compound that reduces the solute solubility, but that is miscible in the first one. The addition of a second compound to the system creates new lactose crystallization conditions to the purity, form and size of the crystals. With this procedure it was intended to get a reasonable control of the lactose crystallization for the improvement of the final quality of the product, that is, a narrow and defined size distribution of the crystals, with homogeneous crystalline habit and guaranteed purity level. Another objective of this work was to study the crystallization system for batch lactose solutions. Very little research has been done on the crystallization process of this complex organic compound, unlike many inorganic products, for which a high quantity of knowledge has been produced. With the accomplishment of the considered study, information had been gotten that make possible to improve the control of the final properties of the crystalline product, such as crystal sizes distribution (CSD), crystalline habit, crystalline fluid inclusions, among others.